Perancangan Aplikasi Pencarian Fasilitas Kesehatan ‘Find Medical’ dengan Menggunakan Metode Haversine dan Algoritma Dijkstra - Elrico Tanto Jaya; Ade Maulana; Jefri Junifer Pangaribuan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
Currently, technology is rapidly advancing, enabling communication to be done with anyone, anywhere. The sophistication of this technology can be utilized to address issues in various fields, particularly in the healthcare sector, as healthcare is one of the most influential aspects of human life. One common problem in the healthcare sector is the lack of evenly distributed information about healthcare services, leading to difficulties for individuals in finding suitable healthcare facilities. Therefore, this research aims to develop an application called